Modelo de workflow de pacientes em ambiente cirúrgico baseado em sistemas de localização em tempo real com RFID - Pessoa, Paulo Manuel (Universidade do Vale do Rio dos Sinos, 2020)
This work deals with patient traceability and room times in a surgical environment, applying Radio-Frequency IDentification technology. Objective is to know where the patient is and the time in the operating room used by the surgeon, recording the information in the patient's chart for later consultations and data collection. This demand arose from a question by the hospital's board whether it was possible to measure a patient's office time automatically. The model was implemented in a simulated environment due to the pandemic, using the application methodology, the data captured by the antenna were recorded in the hospital's database through a Virtual Private Network. The data obtained and the improvements made in the tests were described to obtain the best results with the equipment used. In the end, a satisfactory result was shown with the 140º antenna capturing distances of up to 5 meters, which can be improved with more financial investments for the acquisition of more equipment.
Keywords: RFID; Sensor; Localização; Sistemas distribuídos; Informática médica; Location; Distributed systems; Medical informatics